O Desenvolvimento do Poder Local em África: O caso dos municípios em Moçambique - José António Oliveira Rocha; Gonçalves Jonas Bernardo Zavale (Cadernos de Estudos Africanos)
Mozambique, an African country colonized by Portugal, had a local dual administration, that is, Africans were managed by Traditional Authorities (or Régulos) while Europeans and Africans considered assimilated were grouped into municipalities. After independence the country was heavily centralized and abolished administrative dualism. In the nineties it reborn the distinction between rural and urban areas (desconcentrated) with local power. The result is not very different from the colonial period; in fact Portuguese laws were reimported. So we can talk of a prismatic administrative theory (Riggs, 1964).